Caribbean military encounters - Puri, Shalini; Putnam, Lara (New Caribbean studies, 2017)
This book provides a much-needed study of the lived experience of militarization in the Caribbean from 1914 to the present. Rather than opposing or defending militarization per se, this book focuses attention on how Caribbean people negotiate militarization in their everyday lives.